Human model of burn injury that quantifies the benefit of cooling as a first aid measure - Wright, EH; Tyler, M; Vojnovic, B; Pleat, J; Harris, A; Furniss, D (Wiley, 2019)
Background Burn injuries are a major cause of morbidity and mortality worldwide. Cooling is widely practised as a first aid measure, but the efficacy of cooling burns in human skin has not been demonstrated. A safe, consistent, ethically acceptable model of burning and cooling in live human skin in vivo was developed, and used to quantify the effects of cooling. Methods Novel apparatus was manufactured to create and cool burns in women who were anaesthetized for breast reconstruction surgery using a deep inferior epigastric artery perforator flap. Burns were excised between 1 and 3 h after creation, and analysed using histopathological assessment. Results All 25 women who were approached agreed to take part in the study. There were no adverse events. Increased duration of contact led to increased burn depth, with a contact time of 7·5 s at 70°C leading to a mid‐dermal burn. Burn depth progressed over time following injury, but importantly this was modified by cooling the burn at 16°C for 20 min. On average, cooling salvaged 25·2 per cent of the dermal thickness. Conclusion This study demonstrated the favourable effects of cooling on human burns. Public heath messaging should emphasize cooling as first aid for burns. This model will allow analysis of the molecular effects of cooling burns, and provide a platform for testing novel therapies aimed at reducing the impact of burn injury.